Effect of cryopreservation on growth of different elite embryogenic cell lines of norway spruce (Picea Abies (L.) Karst.) - Dedicova, Beata; Nilsson, O; Egertsdotter, U (2011)
Callus from seven different elite embryogenic cell lines of Norway spruce originated from the controlled crossing conducted by Skogforsk (Forest Research Institute of Sweden) have been cryopreserved in liquid nitrogen using the slow freezing method with sorbitol (0.2 and 0.4 M) and DMSO (5% v/v) as cryoprotectants. Cooloing of samples was performed in a programmable freezer Cryo Med 7452. The cryovials were inserted at +4°C and frozen at -0.3°C/min to -16°C. After 15 min at -16°C, to avoid rapid cooling and crystal formation in the cells, the cryovials were further cooled to -35°C at -0.3°C/min. At the end of the freezing program the cryovials were transferred and stored in a CBS V1500 liquid nitrogen storage unit at -196°C. After thawing and plating on proliferation medium, the recovered cells showed a short lag phase, after which they continued to grow. Lags in growth were also observed after the transfer to pre-maturation and maturation media. Somatic embryo maturation and plantlet regeneration occurred in all the tested embryogenic lines.